Development of an Experimental Animal Model for Lower Back Pain by Percutaneous Injury‐Induced Lumbar Facet Joint Osteoarthritis. Issue 11 (November 2015) - Kim, Jae‐Sung; Ahmadinia, Kasra; Li, Xin; Hamilton, John L.; Andrews, Steven; Haralampus, Chris A.; Xiao, Guozhi; Sohn, Hong‐Moon; You, Jae‐Won; Seo, Yo‐Seob; Stein, Gary S.; Van Wijnen, Andre J.; et al.
<x xml:space="preserve">Abstract</x> We report generation and characterization of pain‐related behavior in a minimally invasive facet joint degeneration (FJD) animal model in rats. FJD was produced by a non‐open percutaneous puncture‐induced injury on the right lumbar FJs at three consecutive levels. Pressure hyperalgesia in the lower back was assessed by measuring the vocalization response to pressure from a force transducer. After hyperalgesia was established, pathological changes in lumbar FJs and alterations of intervertebral foramen size were assessed by histological and imaging analyses. To investigate treatment options for lumber FJ osteoarthritis‐induced pain, animals with established hyperalgesia were administered with analgesic drugs, such as morphine, a selective COX‐2 inhibitor, a non‐steroidal anti‐inflammatory drug (NSAID) (ketorolac), or pregabalin. Effects were assessed by behavioral pain responses. One week after percutaneous puncture‐induced injury of the lumbar FJs, ipsilateral primary pressure hyperalgesia developed and was maintained for at least 12 weeks without foraminal stenosis. Animals showed decreased spontaneous activity, but no secondary hyperalgesia in the hind paws. Histopathological and microfocus X‐ray computed tomography analyses demonstrated that the percutaneous puncture injury resulted in osteoarthritis‐like structural changes in the FJs cartilage and subchondral bone. Pressure hyperalgesia was completely reversed by morphine. The administration of celecoxib produced moderate pain reduction with no statistical significance while the administration of ketorolac and pregabalin produced no analgesic effect on FJ osteoarthritis‐induced back pain. Our animal model of non‐open percutanous puncture‐induced injury of the lumbar FJs in rats shows similar characteristics of low back pain produced by human facet arthropathy. J. Cell. Physiol. 9999: 2837–2847, 2015. © 2015 Wiley Periodicals, Inc.